Influencing Purchase Intention of Korean Cosmetics in Payakumbuh - Winny Marlina; Renada Amalia; Suci Fresti Putri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The growing K-beauty trend due to the influence of Hallyu or Korean Wave which represents the spread of South Korean culture globally, including in terms of beauty standards. This phenomenon highlights the concept of South Korean beauty that prioritizes a fresh and natural appearance through the use of makeup. This study aims to see the effect of social media effectiveness, country of origin, brand image, on purchase intentions moderated by halal product knowledge on South Korean cosmetics in Payakumbuh City. A quantitative approach was used in this study, data were analyzed using SEM-PLS with a sample size of 194 people. The results showed that Information Accuracy, Brand Credibility, had a significant positive effect, but information quality and source credibility did not affect the Effectiveness of Social Media Communication, country of origin and brand image variables had a positive and significant relationship direction to purchase intentions. Moderation of halal product knowledge did not moderate the relationship between country of origin and purchase intentions, halal product knowledge increased the relationship between brand image and purchase intentions.